Evidence for an extensive ice shelf in northern Baffin Bay during the Last Glacial Maximum - Pierre-Olivier Couette; Patrick Lajeunesse; Jean-François Ghienne; Boris Dorschel; Catalina Gebhardt; Dierk Hebbeln; Etienne Brouard (Communications Earth & Environment, 2022)
A large moraine system extends along the continental slope of Baffin Island, Canada, according to swath bathymetry and acoustic profiler data, which suggests that an ice shelf of 500 m thickness covered Baffin Bay during the Last Glacial Maximum.